2012
DOI: 10.1149/2.106204jes
|View full text |Cite
|
Sign up to set email alerts
|

PtCu3, PtCu and Pt3Cu Alloy Nanoparticle Electrocatalysts for Oxygen Reduction Reaction in Alkaline and Acidic Media

Abstract: Dealloying of Pt bimetallic nanoparticles is a promising synthesis method to prepare highly active electrocatalysts for oxygen reduction reaction (ORR) in alkaline and acidic PEM fuel cells. We present here a structural, compositional and electrochemical characterization linked with ORR activity for carbon supported PtCu 3 , PtCu, and Pt 3 Cu alloy nanoparticles in different electrolytes and pH values. The effects of electrolyte and pH are systematically examined on the ECSA and Pt mass based activity (j mass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
168
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 235 publications
(180 citation statements)
references
References 80 publications
11
168
0
1
Order By: Relevance
“…Отметим, что после термической обработки при 350 • C на рентгенограмме появляются дополнитель-ные отражения при значениях 2θ ∼ 20.7, 53.2, 73.4 • , которые не связаны с оксидами или гидроксидами меди. Одним из возможных объяснений появления этих мак-симумов является формирование сверхструктуры, т. е. образование наночастиц со структурой интерметаллида состава PtCu в процессе нагрева и последующего мед-ленного охлаждения [7,16]. Отметим, что формирование упорядоченной структуры интерметаллида, по мнению ряда авторов, может приводить к повышению каталити-ческой активности [7].…”
Section: результатыunclassified
“…Отметим, что после термической обработки при 350 • C на рентгенограмме появляются дополнитель-ные отражения при значениях 2θ ∼ 20.7, 53.2, 73.4 • , которые не связаны с оксидами или гидроксидами меди. Одним из возможных объяснений появления этих мак-симумов является формирование сверхструктуры, т. е. образование наночастиц со структурой интерметаллида состава PtCu в процессе нагрева и последующего мед-ленного охлаждения [7,16]. Отметим, что формирование упорядоченной структуры интерметаллида, по мнению ряда авторов, может приводить к повышению каталити-ческой активности [7].…”
Section: результатыunclassified
“…Differences in the diffusion-limited current densities could be attributed to the unequal electrode coverage with catalyst [27]. The onset and half wave (E 1/2 ) potentials of the ORR polarization curve are often used to compare the electrocatalytic activity of different electrocatalysts.…”
Section: 3electrochemical Characterizationmentioning
confidence: 99%
“…On the other hand, particular consideration and extensive attention of researchers have been given to PEMFCs due to their environmental friendly characteristics, high power density and low operation temperature [1][2][3][4][5][6][7][8][9][10][11][12][13]. Currently carbon supported Pt nanoparticles are extensively used as electrocatalysts in PEMFCs.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, Pt-Cu alloy nanoparticles are catalyzing the attention as cathodic electrocatalysts in PEMFC due to significant improving of the ORR activity [1][2][3][4][5][6][7][8][9]20]. Liu et al [6] developed metallic PtCu multi-nanorods and reported an enhanced electrocatalytic activity and stability for ORR compared to conventional Pt/C catalysts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation